Ytterbium-doped proton conductor fuel cell cathode material as well as preparation method and application thereof
Through the cathode material of ytterbium-doped proton conductor fuel cell, the cathode material has poor catalytic activity and oxygen vacancies formed at medium and low temperatures, and has significantly improved the tolerance to carbon dioxide and the overall performance of the battery.
Patent Information
- Application Number
- CN202411892273.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
The cathode material of proton conductor fuel cell has poor catalytic activity at medium and low temperatures, and the problems of oxygen vacancies and carbon dioxide-induced degradation seriously affect the stability and performance of the battery.
The cathode material of the proton conductor fuel cell using ytterbium-doped proton conductor is BaCo0.4Fe0.4Zr0.1Y0.1-xYbxO3-δ. Yb is doped into the matrix material by sol-gel method to prepare a cathode material with a single, pure cubic perovskite structure.
Reduce oxygen vacancies concentration, improve material tolerance to carbon dioxide, enhance structural stability, improve reduction reaction activity, reduce polarization resistance, and improve the electrochemical performance of the battery.
Smart Images

Figure CN119650726A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of proton conductor fuel cells, and in particular to an ytterbium-doped proton conductor fuel cell cathode material and a preparation method and application thereof. Background Art
[0002] Proton conductor fuel cells (PCFCs) have broad application prospects as an efficient and clean energy conversion device. Solid oxide fuel cells are capable of generating electricity efficiently from a variety of fuels and are a promising technology to alleviate the growing global energy demand, characterized by high energy conversion efficiency, low emissions, and good fuel flexibility. The high operating temperature and activation energy of oxygen ion electrolytes such as yttrium-stabilized zirconia have hindered the practical commercial application of solid oxide fuel cells, because high temperatures (>800°C) usually mean high costs, expensive dedicated materials, technical complexity, and obvious performance degradation in long-term operation. Therefore, proton conductor fuel cells can reduce the operating conditions of solid oxide fuel cells to the low temperature range (300-600°C), which can overcome the shortcomings of oxygen ion conductors and also bring more industrial prospects, such as cheap interconnection and long-term electrochemical stability.
[0003] However, its cathode materials face many challenges in practical applications, such as the formation of oxygen vacancies and carbon dioxide-induced degradation, which seriously affect the stability and performance of the battery. Summary of the invention
[0004] The purpose of the present invention is to provide an ytterbium-doped proton conductor fuel cell cathode material and a preparation method and application thereof, which improves the shortcomings of the material such as poor catalytic activity at medium and low temperatures and insufficient tolerance to CO2 by reducing oxygen vacancies.
[0005] In one aspect of the present invention, the present invention provides an ytterbium-doped proton conductor fuel cell cathode material. According to an embodiment of the present invention, the chemical formula is BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.1-x Yb x O 3-δ , where x represents the molar doping amount of Yb and δ is the oxygen vacancy content.
[0006] In addition, the ytterbium-doped proton conductor fuel cell cathode material according to the above embodiment of the present invention may also have the following additional technical features:
[0007] In some embodiments of the present invention, the value of x is 0.05 or 0.1, and the chemical formula of the cathode material is BaCo 0.4 Fe 0.4 Zr0.1 Y 0.05 Yb 0.05 O 3-δ or BaCo 0.4 Fe 0.4 Zr 0.1 Yb 0.1 O 3-δ .
[0008] In another aspect of the present invention, the present invention provides a method for preparing an ytterbium-doped proton conductor fuel cell cathode material. According to an embodiment of the present invention, the method comprises the following steps: dissolving a barium salt, a cobalt salt, an iron salt, a zirconium salt, a yttrium salt, and an ytterbium salt in a solvent, mixing with a complexing agent, and heating and stirring the solution after adjusting the pH value of the solution until a gel is formed, drying to obtain a precursor, and sintering the precursor to obtain the battery cathode material.
[0009] In addition, the method for preparing a cathode material of a ytterbium-doped proton conductor fuel cell according to the above embodiment of the present invention may also have the following additional technical features:
[0010] In some embodiments of the present invention, the metal salts are all nitrates, the solvent is water, and the complexing agent is citric acid and ethylenediaminetetraacetic acid.
[0011] In some embodiments of the present invention, the molar ratio of the sum of metal ions in the nitrate to citric acid and ethylenediaminetetraacetic acid is 1:2:1.
[0012] In some embodiments of the present invention, the addition amounts of the barium salt, cobalt salt, iron salt, zirconium salt, yttrium salt and ytterbium salt are calculated according to the stoichiometric ratio of the elements in the chemical formula.
[0013] In some embodiments of the present invention, the pH regulator is ammonia water, and the pH value of the solution is adjusted to 7-8; the heating temperature of the stirring is 80°C-100°C; the drying temperature is 200°C-250°C, and the drying time is 4-8h.
[0014] In some embodiments of the present invention, the sintering temperature is 900-1000°C, the heating or cooling rate is 4-6°C / min, the sintering time is 2-4h, and the sintering atmosphere is an oxidizing atmosphere, specifically air or oxygen.
[0015] In another aspect of the present invention, the present invention provides an application of an ytterbium-doped proton conductor fuel cell cathode material. According to an embodiment of the present invention, the battery cathode material is used to prepare an anode-supported single cell in a solid oxide fuel cell.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] 1) The present invention improves the shortcomings of the material such as poor catalytic activity at medium and low temperatures and insufficient tolerance to CO2 by reducing oxygen vacancies, thereby improving the overall performance of PCFC.
[0018] 2) The present invention uses BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.1- O 3-δ As the matrix material, Yb was partially doped into BaCo using the sol-gel method. 0.4 Fe 0.4 Zr 0.1 Y 0.1- O 3-δ The cathode material BaCo with a single, pure cubic perovskite structure was successfully synthesized. 0.4 Fe 0.4 Zr 0.1 Y 0.05 Yb 0.05 O 3-δ 、BaCo 0.4 Fe 0.4 Zr 0.1 Yb 0.1 O 3-δ .
[0019] 3) The present invention significantly improves the tolerance of the material to carbon dioxide by Yb doping. In an environment containing carbon dioxide, the structural stability of the material is enhanced, effectively avoiding the performance degradation caused by carbon dioxide.
[0020] 4) Reducing the oxygen vacancy concentration while increasing the reduction reaction (ORR) activity, reducing the polarization resistance and improving the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 XRD comparison spectra of BCFZYb, BCFZYYb, and BCFZY prepared in Examples 1-2 of the present invention and the comparative example;
[0022] Figure 2 Schematic diagram of thermal expansion curves of BCFZYb, BCFZYYb, and BCFZY prepared in Examples 1-2 of the present invention and the comparative example;
[0023] Figure 3 Schematic diagram of the conductivity of BCFZYb, BCFZYYb, and BCFZY prepared in Examples 1-2 of the present invention and the comparative example;
[0024] Figure 4 It is a XPS schematic diagram of BCFZYb, BCFZYYb, and BCFZY prepared in Examples 1-2 of the present invention and the comparative example;
[0025] Figure 5 Thermogravimetric loss graphs of BCFZYb, BCFZYYb, and BCFZY prepared in Examples 1-2 of the present invention and Comparative Examples;
[0026] Figure 6 XRD comparison spectra of BCFZYb, BCFZYYb, and BCFZY prepared in Examples 1-2 of the present invention and the comparative example after being treated in a 1% CO2 atmosphere for 24 hours;
[0027] Figure 7 The power density diagram of three single cells prepared for the application examples of the present invention at 550°C;
[0028] Figure 8 Impedance diagrams of three single cells prepared for application examples of the present invention at 550°C;
[0029] Fig. 9 This is a stability test of a single cell prepared using BCFZYb at 550°C as an application example of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] BaCo, a ytterbium-doped proton conductor fuel cell cathode material 0.4 Fe 0.4 Zr 0.1 Yb 0.1 O 3-δ The preparation method comprises the following steps:
[0033] According to the stoichiometric ratio of the elements in the chemical formula, weigh 1 mol of barium nitrate Ba(NO3)2, 0.4 mol of cobalt nitrate (Co(NO3)2·6H2O), 0.4 mol of iron nitrate Fe(NO3)2·9H2O, 0.1 mol of zirconium nitrate Zr(NO3)4·5H2O, and 0.1 mol of ytterbium nitrate Yb(NO3)3·6H2O, respectively, and then add them to a beaker containing an appropriate amount of deionized water, heat to 90°C, and stir with a magnetic stirrer until the solution is completely dissolved. According to the molar ratio of the sum of metal ions to citric acid and ethylenediaminetetraacetic acid of 1:2:1, weigh ethylenediaminetetraacetic acid and citric acid and add them to the above nitrate solution, and continue to add ammonia water to adjust the pH until the solution is neutral (pH=7). Continue heating and stirring until the solution becomes a viscous colloid, put it in a drying oven and dry it for 6 hours to obtain a fluffy precursor powder. The fluffy powder was placed in a crucible and then placed in a muffle furnace for sintering at 950°C for 2 hours at a heating rate of 5°C / min in an air atmosphere. The target powder BaCo 0.4 Fe 0.4 Zr 0.1 Yb 0.1 O 3-δ , denoted as BCFZYb.
[0034] Example 2
[0035] BaCo, a ytterbium-doped proton conductor fuel cell cathode material 0.4 Fe 0.4 Zr 0.1 Y 0.05 Yb 0.05 O 3-δ The preparation method of the present invention is different from that of Example 1 only in that the contents of barium nitrate Ba(NO3)2, cobalt nitrate (Co(NO3)2·6H2O), iron nitrate Fe(NO3)2·9H2O, and zirconium nitrate Zr(NO3)4·5H2O remain unchanged, and 0.1 mol of yttrium nitrate Y(NO3)3·6H2O is replaced by 0.05 mol of ytterbium nitrate Yb(NO3)3·6H2O and 0.05 mol of yttrium nitrate Y(NO3)3·6H2O. Finally, cathode material powder BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.05 Yb 0.05 O 3-δ , denoted as BCFZYYb.
[0036] Comparative Example
[0037] BaCo, a proton conductor fuel cell cathode material 0.4 Fe 0.4 Zr 0.1 Y 0.1O 3-δ The preparation method of the present invention is different from that of Example 1 only in that the contents of barium nitrate Ba(NO3)2, cobalt nitrate (Co(NO3)2·6H2O), iron nitrate Fe(NO3)2·9H2O, and zirconium nitrate Zr(NO3)4·5H2O remain unchanged, and 0.1 mol of ytterbium nitrate Yb(NO3)3·6H2O is replaced by 0.1 mol of yttrium nitrate Y(NO3)3·6H2O. Finally, cathode material powder BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.1 O 3-δ Cathode material powder, denoted as BCFZY.
[0038] The cathode materials prepared in Examples 1-2 and Comparative Examples were characterized by XRD. Figure 1 As shown in the figure, no impurity phase was found in the product BCFZYb. The incorporation of Yb caused the main peak of XRD to move significantly to a high angle, indicating that the lattice of the perovskite was shrinking. This may be because Yb 3+ The ionic radius of (0.086nm) is smaller than that of Y 3+ (0.090nm).
[0039] The cathode materials prepared in Examples 1-2 and the comparative example were tested for thermal expansion coefficient. 2.5g of sample powder was pressed into a cuboid by dry pressing method at a pressure of 120Mpa, and sintered into a dense cuboid at 1100°C. The heating rate was 5°C / min and the sintering time was 5 hours. The thermal expansion coefficient of the sample was tested at 500-800°C in air atmosphere. The initial length L0 of the block and the length L at different temperatures were measured, and the curve of (dL / L0) changing with temperature was plotted to obtain the thermal expansion coefficient curve of the sample. Figure 2 As shown, BCFZYb(19.8×10 -6 K -1 ) showed a slightly lower average TEC than BCFZY (22.9×10 -6 K -1 ), indicating that the introduction of a small amount of Yb to replace Y at the B site slightly improves the TEC of the perovskite material.
[0040] The cathode materials prepared in Examples 1-2 and the comparative example were tested for conductivity. 1g of sample powder was pressed into a cuboid by dry pressing at a pressure of 120 MPa, and sintered into a dense cuboid at 1100°C with a heating rate of 5°C / min and a sintering time of 5 hours. The test temperature range was 300-800°C. Figure 3As shown, for all three samples, the conductivity increases with increasing temperature, indicating a typical p-type semiconductor behavior. Obviously, the conductivity increases with the substitution of Yb. The electronic conductivity of cubic perovskite is mainly related to the hole hopping process. The excessive generation of oxygen vacancies may eliminate the concentration of holes, thereby hindering the hole hopping on the Fe(Co)-O-Fe(Co) bond. The improvement of electronic conductivity also means that Yb doping suppresses the generation of oxygen vacancies.
[0041] The cathode materials prepared in Examples 1-2 and Comparative Examples were subjected to XPS testing to characterize oxygen vacancies, such as Figure 4 As shown in Figure 2, the ratio of lattice oxygen to adsorbed oxygen in BCFZYb (O la / O ad )(~0.43) is higher than that of BCFZYYb(~0.41) and BCFZY(~0.38), indicating that the oxygen vacancy concentration decreases with the increase of Yb doping amount.
[0042] The thermogravimetric loss of the cathode materials prepared in Examples 1-2 and the comparative example was characterized, and the test range was from room temperature to 1000°C, and the heating rate was 10°C / min, and the thermodynamic mass loss at high temperature was tested. Figure 5 It can be seen that with the increase of Yb doping amount, the oxygen vacancy concentration decreases, which is consistent with the XPS characterization results.
[0043] The cathode materials prepared in Examples 1-2 and Comparative Example were treated at 600° C. for 24 hours in a 1% CO2 environment and then subjected to XRD analysis to observe their structural changes, such as Figure 6 As shown, after CO2 treatment, obvious diffraction peaks corresponding to barium carbonate exist in BCFZY and BCFZYYb, while they are absent in the BCFZYb sample, proving that BCFZYb has better CO2 tolerance.
[0044] Application Examples
[0045] The electrode materials prepared in Examples 1-2 and Comparative Example were assembled into anode-supported solid oxide electrochemical cell cells, and the electrolyte was BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ (BZCYYb for short), the anode material is NiO-BZCYYb, NiO and BaZr in the anode material 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δThe mass ratio of is 6:4, and the cathode materials are the electrode materials prepared in Examples 1-2 and Comparative Example, respectively, to obtain an anode-supported single cell NiO-BZCYYb / BZCYYb / BCFZYb (BCFZYYb, BCFZY).
[0046] The electrochemical impedance spectra of the battery were obtained using an impedance analyzer (Solartron 1260) with a test frequency range of 0.1 Hz-1 MHz. The IV and IP curves of the single cell were obtained using a source measure instrument based on a four-probe configuration (Keithley 2400).
[0047] The output power of a single cell at 550°C is characterized, as Figure 7 As shown in Figure 2, the peak power densities of the three cathode materials BCFZY, BCFZYYb and BCFZYb at 550 °C were 643 mW cm -2 、524mW·cm -2 and 443 mW·cm -2 .
[0048] The AC impedance spectrum of the single cell at 550°C was characterized, as shown in Figure 8 As shown. The BCFZYb-based single cell shows a lower polarization resistance than BCFZYYb and BCFZY. At 550°C, the polarization resistances of BCFZY, BCFZYYb, and BCFZYb are 0.264Ω·cm 2 、0.183Ω·cm 2 、0.112Ω·cm 2 .
[0049] The stability of the BCFZYb battery was tested at 550°C. Fig. 9 The single cell with BCFZYb as cathode can be operated stably at 550 °C for about 900 h without obvious degradation.
[0050] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. An ytterbium-doped proton conductor fuel cell cathode material, characterized in that: Its chemical formula is BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.1-x Yb x O 3-δ , where x represents the molar doping amount of Yb and δ is the oxygen vacancy content.
2. The ytterbium-doped proton conductor fuel cell cathode material according to claim 1, characterized in that: The value of x is 0.05 or 0.1, and the chemical formula of the cathode material is BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.05 Yb 0.05 O 3-δ or BaCo 0.4 Fe 0.4 Zr 0.1 Yb 0.1 O 3-δ .
3. A method for preparing the ytterbium-doped proton conductor fuel cell cathode material according to claim 1, characterized in that: The method comprises the following steps: dissolving barium salt, cobalt salt, iron salt, zirconium salt, yttrium salt and ytterbium salt in a solvent, mixing with a complexing agent, adjusting the pH value of the solution, heating and stirring the solution until a gel is formed, drying to obtain a precursor, and sintering the precursor to obtain the battery cathode material.
4. The method for preparing an ytterbium-doped proton conductor fuel cell cathode material according to claim 3, characterized in that: The metal salts are all nitrates, the solvent is water, and the complexing agents are citric acid and ethylenediaminetetraacetic acid.
5. The method for preparing an ytterbium-doped proton conductor fuel cell cathode material according to claim 4, characterized in that: The molar ratio of the sum of metal ions in the nitrate to citric acid and ethylenediaminetetraacetic acid is 1:2:
1.
6. The method for preparing an ytterbium-doped proton conductor fuel cell cathode material according to claim 3, characterized in that: The addition amounts of the barium salt, cobalt salt, iron salt, zirconium salt, yttrium salt and ytterbium salt are calculated according to the stoichiometric ratio of the elements in the chemical formula.
7. The method for preparing a cathode material of a ytterbium-doped proton conductor fuel cell according to claim 3, characterized in that: The pH value of the solution is adjusted to 7-8; the heating temperature of the stirring is 80°C-100°C; the drying temperature is 200°C-250°C, and the drying time is 4-8h.
8. The method for preparing an ytterbium-doped proton conductor fuel cell cathode material according to claim 3, characterized in that: The sintering temperature is 900-1000° C., the heating or cooling rate is 4-6° C. / min, the sintering time is 2-4 hours, and the sintering atmosphere is an oxidizing atmosphere.
9. An application of the ytterbium-doped proton conductor fuel cell cathode material according to any one of claims 1 to 2, characterized in that: The battery cathode material is used for preparing an anode-supported single cell or a symmetrical cell in a solid oxide fuel cell.